2017
DOI: 10.5056/jnm16183
|View full text |Cite
|
Sign up to set email alerts
|

Future Treatment of Constipation-associated Disorders: Role of Relamorelin and Other Ghrelin Receptor Agonists

Abstract: There is an unmet need for effective pharmacological therapies for constipation, a symptom that significantly deteriorates patients' quality of life and impacts health care. Ghrelin is an endogenous ligand for the growth hormone secretagogue receptor and has been shown to exert prokinetic effects on gastrointestinal (GI) motility via the vagus and pelvic nerves. The pharmacological potential of ghrelin is hampered by its short half-life. Ghrelin receptor (GRLN-R) agonists with enhanced pharmacokinetics were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Studies indicated that the synthetic ghrelin agonist relamorelin may be effective in increasing stool frequency and accelerating colonic transit. 76 However, so far marketing authorization for relamorelin in constipation has not been granted. Recently, the Parkinson study group could not detect significant clinical benefits for relamorelin in PD-associated constipation which may, however, be attributed to the failure of meeting the recruitment target.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that the synthetic ghrelin agonist relamorelin may be effective in increasing stool frequency and accelerating colonic transit. 76 However, so far marketing authorization for relamorelin in constipation has not been granted. Recently, the Parkinson study group could not detect significant clinical benefits for relamorelin in PD-associated constipation which may, however, be attributed to the failure of meeting the recruitment target.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that ghrelin agonists, with an ability to cross the blood-brain barrier, stimulate colonic prokinetic activity points to the potential usefulness of centrally acting ghrelin agonists for the treatment of patients with chronic constipation (Shimizu et al, 2006;Shafton et al, 2009;Avau et al, 2013;Pustovit et al, 2014;Acosta et al, 2015;Mosi nska et al, 2017). Thus, we investigated whether a novel ghrelin agonist with the ability to penetrate the blood-brain barrier (HM01) had any effect on delayed GI motility.…”
Section: Discussionmentioning
confidence: 99%
“…The GI prokinetic effects of ghrelin occur through two mechanisms: a direct peripheral effect on ghrelin receptors within the myenteric plexus or via ghrelin receptors on the vagus and pelvic nerves activating a centrally mediated mechanism. The upper GI prokinetic effects are thought to activate peripheral ghrelin receptors in the enteric nervous system, whereas the accelerated colonic transit induced by ghrelin itself or ghrelin mimetics likely occurs through a central site of action via vagal and pelvic nerves (Binn et al, 2006;Pustovit et al, 2014;Mosi nska et al, 2017). However, a study in guinea pigs suggested that the contribution of peripheral enteric ghrelin receptors in the stimulation of upper GI transit is modest, and that the gastrostimulatory action of ghrelin can occur through activation of capsaicinsensitive extrinsic vago-vagal reflex pathways (Nakamura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, in patients undergoing intestinal resection, ipamorelin does not shorten the time for the first meal intake compared to placebo [30]. The Phase II clinical trial below showed no significant difference in measurable colonic functions between ipamorelin and placebo [31]. Due to these disappointing results, its development was halted.…”
Section: Ipamorelinmentioning
confidence: 98%